2018
DOI: 10.1177/1534508418808598
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric Fundamentals of the Social Skills Improvement System: Social–Emotional Learning Edition Rating Forms

Abstract: This study described the development of the Social Skills Improvement System Social Emotional Learning Edition Rating Forms (SSIS SEL RF) for teachers, parents, and students. This new multirater assessment is a reconfiguration of the SSIS Rating Scales items inspired by the CASEL Social Emotional Competency framework. The internal structure and score reliability estimates were examined across three raters for a common sample of more than 200 individual children ages 3 to 18 years. Confirmatory factor analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 29 publications
6
64
1
4
Order By: Relevance
“…Overall, our findings and those reported elsewhere Gresham et al, 2020;Panayiotou et al, 2019) suggest that currently the SSIS is unable to meaningfully capture distinct domains of social skills (or social-emotional competence in the case of SSIS-SEL). This does not necessarily mean, however, that the poor discriminant validity of the measure is the result of a common general factor.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Overall, our findings and those reported elsewhere Gresham et al, 2020;Panayiotou et al, 2019) suggest that currently the SSIS is unable to meaningfully capture distinct domains of social skills (or social-emotional competence in the case of SSIS-SEL). This does not necessarily mean, however, that the poor discriminant validity of the measure is the result of a common general factor.…”
Section: Discussioncontrasting
confidence: 61%
“…Results pointed to two issues. First, as with the original study (Gresham et al, 2020), this model was shown to have inconsistent fit, with respect to CFI and RMSEA, χ 2 (979) = 3355.421, p < .001; RMSEA = .028 (90% CI [.027, .029]), p > .05; CFI = .888, TLI = .881, SRMR = 053. Strictly following the minimum acceptable cutoffs, it appeared to fit the data well in terms of RMSEA, but poorly when CFI was considered.…”
Section: Ssis-sel Structurementioning
confidence: 71%
See 1 more Smart Citation
“…Behavior rating scales are among the most frequently used measures of social behavior in school and clinical settings (Achenbach & Rescorla, ; Gresham & Elliott, , ; Kamphaus & Reynolds, ). Behavior rating scales are considered indirect measures of behavior because they are not measuring behavior at a time and place of its actual occurrence.…”
Section: Assessment Of Sel Skills: Advantages Of Behavior Rating Scalesmentioning
confidence: 99%
“…The purpose of the present study is to systematically explore patterns of agreement among teachers, parents, and students across several SEL competence domains. This investigation used the revision of the SSIS SEL edition rating forms (Gresham & Elliott, ). The SSIS SEL edition rating forms represents a multirater (teacher, parent, and student) series of rating forms to assess the frequency of SEL skills (see details regarding these assessments in the Instrumentation section).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%